Ecuador : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2003)
This Selected Issues paper and Statistical Appendix analyzes Ecuador's fiscal policy using the concepts of the fiscal stance and fiscal impulse adjusted for movements in the real effective exchange rate. It finds that fiscal policy has been expansionary in 2000 and 2001. The paper shows that the growth of gross fixed investment was relatively strong during the 1970s; thereafter it slowed, particularly in the public sector. The paper also explores the evolution of oil reserves in recent years and the projections for the medium term.